Population parameters of golden ponyfish, Photopectoralis aureus and goldstripe ponyfish, Karalla daura from Saint Martin Island, Bay of Bengal (Research in Agriculture Livestock and Fisheries, 2024)
Golden ponyfish Photopectoralis aureus and Goldstripe ponyfish Karalla daura are small fish with less economic value. Many marine fish population parameters were not investigated because of their low commercial value. Therefore, the primary goals of this study were to determine the size frequency, length-weight relationship (LWR), length-length relationship (LLR), and Fulton’s condition factor (Kn) of two tropical ponyfishes from Saint Martin’s Island. From March to April 2022, specimens were caught using fixed purse nets. A total of 409 specimens of P. aureus and K. daura were measured to determine size frequency, LWRs, LLRs, and Fulton's condition factor. For P. aureus, the maximum total length (TL) of 12.9 cm sets a new record. The LWRs for P. aureus and K. daura were highly significant (p